Microglia in Alzheimer's Disease: Risk Factors and Inflammation - Katsumoto, Atsuko; Takeuchi, Hideyuki; Takahashi, Keita; Tanaka, Fumiaki (Frontiers in Neurology, 2018)
Microglia are resident immune cells in the central nervous system (CNS) that originate from myeloid progenitor cells in the embryonic yolk sac and are maintained independently of circulating monocytes throughout life. In the healthy state, microglia are highly dynamic and control the environment by rapidly extending and retracting their processes. When the CNS is inflamed, microglia can give rise to macrophages, but the regulatory mechanisms underlying this process have not been fully elucidated. Recent genetic studies have suggested that microglial function is compromised in Alzheimer’s disease (AD), and that environmental factors such as diet and brain injury also affect microglial activation. In addition, studies of triggering receptor expressed on myeloid cells 2–deficiency in AD mice revealed heterogeneous microglial reactions at different disease stages, complicating the therapeutic strategy for AD. In this paper, we describe the relationship between genetic and environmental risk factors and the roles of microglia in AD pathogenesis, based on studies performed in human patients and animal models. We also discuss the mechanisms of inflammasomes and neurotransmitters in microglia, which accelerate the development of amyloid-β and tau pathology.